The Writing Teacher's Guide to Pedagogical Documentation Rethinking How We Assess Learners and Learning - Stockman, Angela (Routledge Taylor & Francis Group, 2024)
This book is a call to action for English and English Language Arts teachers who understand that data are not numbers alone, that learning is impossible to quantify, and that students are our very best teachers. Writing teacher Angela Stockman shows us how pedagogical documentation-the practice of making learning visible, capturing what is seen and heard, and then, interpreting those findings in the company of our students and our colleagues-is a humbling and humane practice that grounds what we think we've come to know in the lived experiences of those we intend to serve. In this rich resource, she offers... processes and protocols for documenting learning and analyzing data; resources and planning tools to help you design and execute your own projects; and a digital documentation notebook that you can download for guidance, inspiration, and examples. With the powerful tools in this book, you'll be inspired to reach students whose needs have been ignored by big data and whose identities have been erased by oppressive forms of assessment and evaluation